Surgical management of hyperdivergent Class II malocclusion with vertical maxillary excess: A 2-year follow-up - Nayeemullah Khan; K Moina Adeni; Ratna Parameswaran; Devaki Vijayalakshmi (Wolters Kluwer Medknow Publications, 2018)
Skeletal Class II malocclusions with vertical maxillary excess (VME) present with an amalgamation of several problems pertaining to psychological, esthetics, and function. The optimal treatment plan in such cases includes a synchronized orthodontic-surgical approach through superior repositioning and setback of maxilla by means of Le Fort I osteotomy and augmentation genioplasty. This case report describes a multidisciplinary approach in the successful management of a patient with VME to achieve superior esthetics and function.